The risk of recurrent venous thromboembolism in patients with unprovoked symptomatic deep vein thrombosis and asymptomatic pulmonary embolism - Jiménez, David; Díaz, Gema; Marín, Elena; Vidal, Rafael; Sueiro, Antonio; Yusen, Roger D. (Thrombosis and Haemostasis, 2006)
Patients with a first episode of symptomatic pulmonary embolism (PE) havea higher risk of recurrent venous thromboembolism (VTE) than patients with a first episode of proximal lower extremity deep vein thrombosis (DVT). Patients with symptomatic DVT and silent PE may havea different risk of VTE recurrence than patients that have symptomatic DVT without PE. Therefore, it was the aim of this prospective cohort study to compare the risk of recurrent symptomaticVTE in patients with proximal lower extremity DVT and silent PE to the risk in patients that only have proximal lower extremity DVT. Ninty-one consecutive outpatients presenting to the emergency department of a university hospital subsequently hospitalised with a first episode of unprovoked symptomatic proximal lower extremity DVT, and without new pulmonary symptoms were included. Standard initial treatment consisted of intravenous unfractionated heparin or subcutaneous low-molecular-weight heparin for 5–7 days, overlapped with oral vitamin-K antagonist therapy, with long-term oral vitamin-K antagonist therapy (goal INR 2.5 [2.0–3.0]). Study endpoints were: symptomatic recurrent DVT, new PE, and recurrent PE, evaluated by standard objective testing. At enrolment, 28 of 91 (31%) patients with DVT had silent PE. In the patients with DVT and silent PE, there were 3 VTE recurrences during 20 person-years of follow-up, while there were no VTE recurrences during 61 person-years of follow-up in the patients with isolated DVT. The Kaplan-Meier estimated VTE recurrence rate at 1 year after the diagnosis of DVT was 11% (95% CI: 2–28%) for patients with symptomatic DVT and silent PE, compared to 0% in patients with isolated symptomatic DVT (p = 0.0045). In patients with a first episode of unprovoked symptomatic acute proximal lower extremity DVT, the risk of recurrent VTE was significantly higher in those with silent PE compared to those without PE.
Keywords: Clinical/epidemiological studies; pulmonary embolism; deep vein thrombosis